Determination of the intrinsic diffusivities from the diffusion couple experiment in multicomponent systems. (September 2017) - Zajusz, Marek; Dąbrowa, Juliusz; Danielewski, Marek
Abstract: A new method, which allows determination of intrinsic diffusivities values on the Kirkendall plane in multicomponent systems, is presented. The approach is based on the zero contribution of drift flux to the total flux value of i -th component, when calculated relatively to the Kirkendall plane position. The method allows precise determination of intrinsic diffusivities without limitations of Boltzmann-Matano based methods e.g. in situations when uphill diffusion occurs. The approach is validated on a number of theoretical and experimental systems. The results indicate that the method have a very high potential in application for multicomponent systems, including high entropy alloys. Graphical abstract: